La fin de vers, laboratoire de l’œuvre poétique de l’artiste Josef Albers - Vincent Broqua (Transatlantica)
The writings of Josef Albers (1888-1976) have been obscured by his artistic fame. Through textual analyses, archival material, and a study of his learning of English, this paper explores the poeticity of his writings (poems, statements, treatises on color). In his extended poetry, Albers constructed a new type of line between verse and prose to allow for an experience of the physicality of the text. Run-on-lines and line-endings are the site of this experience.